PRAKTIK GURU DALAM MEMBANGUN IKLIM KELAS POSITIF UNTUK MEWUJUDKAN STUDENT WELL-BEING DI SMA Negeri 11 MUARO JAMBI - Puji Dinda Melati; Friscilla Wulan Tersta; Ferdiaz Saudagar (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze teachers' managerial practices in creating a positive classroom climate to achieve student well-being at SMAN 11 Muaro Jambi. This research uses qualitative research methods with a case study approach. Data collection was conducted thru interviews with subject teachers, guidance and counseling teachers, and students, as well as thru observation and documentation. The research results show that the teacher's managerial practices are carried out thru several stages, namely (1) systematic lesson planning and the formulation of class rules agreements with students. (2) organization thru classroom layout arrangements, seating rotations, and the formation of study groups. (3) lesson implementation, where the teacher applies various teaching media and builds positive interpersonal relationships with students. (4) supervision and evaluation, where the teacher conducts active monitoring and learning reflection. The positive classroom climate built thru the teachers' managerial practices has implications for students' well-being, both psychologically, emotionally, socially, and academically. The success of teachers' managerial practices is supported by school policies, positive interpersonal relationships between teachers and students, teacher professionalism, and collaboration among various parties. As for the inhibiting factors, they include differences in student character and motivation, limitations in facilities and infrastructure, limited time for BK services, and the lack of openness among some students.